PENGARUH ESG DISCLOSURE TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN KEPEMILIKAN INSTITUSIONAL DAN KOMPENSASI EKSEKUTIF SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Indeks KOMPAS100 Indonesia Selama Tahun 2020-2024) - Leander Victorio Demardin; Agus Purwanto (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the effect of Environmental, Social, and Governance Disclosure (ESG) on financial performance, with institutional ownership and executive compensation serving as moderating variables. The research is conducted on companies listed in the KOMPAS100 Index during 2020–2024. The selection of this index is based on its characteristics as a general benchmark of Indonesian capital market performance and as a reference for investors in assessing fundamentally strong stocks. The study employs a quantitative approach using secondary data obtained from annual reports and ESG Disclosure Score data sourced from the Bloomberg Terminal. The sample is selected through purposive sampling, resulting in 120 observations from 24 companies that meet the criteria over the observation period. Financial performance is proxied by Return on Assets (ROA). ESG Disclosure is measured using Bloomberg’s ESG Score on a 0–100 scale. Institutional ownership is measured by the proportion of shares held by institutional investors, while executive compensation is measured using the natural logarithm of total executive compensation. Data analysis is performed using simple linear regression and Moderated Regression Analysis (MRA) with the assistance of IBM SPSS 26.The results indicate three main findings. First, ESG Disclosure has a positive but insignificant effect on ROA. Second, institutional ownership significantly moderates the relationship between ESG Disclosure and ROA, suggesting that stronger institutional monitoring enhances the effectiveness of ESG Disclosure in improving financial performance. Third, executive compensation also significantly moderates the relationship between ESG Disclosure and ROA, indicating that incentive alignment at the executive level strengthens the link between ESG Disclosure and financial performance.